Realtime Remote Programming in Patients Carrying Cardiac Implantable Electronic Devices Requiring Emergent Reprogramming - Xiong, Shiqiang; Li, Jin; Tong, Lin; Hou, Jun; Yang, Siqi; Qi, Lingyao; Chen, Xu; Luo, Yan; Zhang, Zhen; Liu, Hanxiong; Cai, Lin (Frontiers in Cardiovascular Medicine, 2022)
To protect cardiac implantable electronic device (CIED) patients with arrhythmia or possible device malfunction, it is important for health care professionals to provide emergent device evaluation and reprogramming. This case series illustrated the clinical application of realtime remote programming in CIED patients requiring emergent in-person evaluation and reprogramming (ChiCTR2100046883 chictr.org). All remote sessions were performed safely and efficiently by remote electrophysiologists without being in the physical presence of a patient. The implementation of realtime remote programming not only largely reduces the response time to urgent events but also greatly helps to minimize personnel exposure to COVID-19 infection.